(untitled) (Journal of Imam Al-Kadhim College, 2024)
Abstract As a result of the breadth and multiplicity of the knowledge of our contemporary life, we notice the overlapping and intertwining of the growing branches of knowledge, in a way that has become a tangible and undeniable reality, and the intertwining between them has become a clear impact on various aspects of life, especially the field of fine arts, and it has become necessary and urgent to study the conceptual relationships This is what the researcher is trying to address and touch methodologically by approaching the art of the film poster and its artistic design, and the cinematic discourse. Her research included four chapters, the first of which is the methodological framework, which includes the research problem, the importance and need for the research, the research objectives and limitations, and the definition of terminology. In the second chapter, the theoretical framework and previous studies contain two titles, the first is on the elements of building and designing the cinema poster, in which the researcher highlighted the elements of poster design and implementation and some techniques used in the design of the cinema poster, while the second element is on the relationships between poster design and the cinema film, in which the researcher addressed the philosophical, objective and procedural link between the parties involved She also quickly reviewed the historical overview of the beginnings of poster art in general and the cinema poster in particular, pointing out the nature of design and cinema as two distinct fields that have the ability and capacity to link, intertwine and coexist with other knowledge that is intertwined with them in some general conceptual commonalities. The research addressed some previous studies in this discipline and extracted some theoretical indicators for the theoretical framework of the research, which will be used in the process of analyzing the samples selected for this research, after approval by the panel of experts and referees. The third chapter presented the research procedures, which included the research methodology, community, samples, analysis management, reasons for selecting the samples and the unit of analysis used, as well as the analysis of the selected research samples, which are Iraqi, Arab and international samples. The fourth chapter presents the final findings of the research, its final results, and the recommendations that the researcher considers to fulfil the purpose and objectives of the research. This research concludes with a list of sources and scientific references that were relied upon and quoted to support the scientific aspect of the research.